Implementation of the Pentahelix Collaborative Governance Model Minimum Service Standards (SPM) for Health with Hypertension in Local Governments - Rahadian, Mukti Eka; Sanapiah, Abdul Azis; Basseng, Basseng; Asropi, Asropi (Political Science Program, Universitas Negeri Semarang, 2023)
The aim of research is to find factors that cause failure local government in providing access to basic types of services for hypertension sufferers according to SPM to all district residents, formulating appropriate regulations and public administration models and being able to mobilize collaboration among all pentahelix components to provide types of hypertension services according to the SPM, compiling and formulating models and strategies for collaborative collaborative governance, understand the role of facilitative leadership in collaborating across all pentahelix nodes , as well as creating breakthrough innovations in hypertension services. Research uses non-experimental qualitative methods with a case study approach, paying attention to the results of pre-eliminary studies , empirical facts and magnitude of public problems. Application of the pentahelix collaborative governance model has proven effective in increasing coverage of SPM for hypertension. Effective regulations consist of a regent's decision letter regarding the implementation of the pentahelix collaborative governance model, determining sub-district locus and a social contract between regent and all champions pentahelix. Cooperation model, roles and technical responsibilities of hypertension services for each pentahelix component at district, sub-district, village and RT/RW regional government levels, are regulated using a conceptual framework and business process standard for governance flow and reporting flow for implementation of pentahelix collaborative governance model . Facilitative and innovative leadership is the key to the success of Pentahelix collaboration in providing types of hypertension services that are easily accessible to all district residents.